Implementation of The Electronic Application for Marriage and Pregnancy (Elsimil) to Accelerate Stunting Reduction - Ida Ayu Komang Wulansari; Ida Ayu Oka Martini; Gede Sri Darma; Luh Putu Mahyuni (Jurnal Penelitian Pendidikan IPA, 2024)
Denpasar City is one of the areas that has succeeded in reducing the prevalence to 5.5%, one of which is by providing guidance to prospective brides to reduce the risk of stunting cases by implementing the ELSIMIL application. This study was conducted to obtain an overview of the factors that influence the behavior of using the ELSIMIL application in Denpasar City so that it can be an effort to accelerate stunting reduction. Data were collected from 14 informants, both users and policy holders. Data collection methods through interviews, observations, and document studies with validity testing through source triangulation and method triangulation. The results of the description of the ELSIMIL application implementation show that performance expectations, effort expectations, social influences, and facility conditions affect usage behavior along with behavioral intentions according to UTAUT theory. Performance expectations, which include perceived usefulness, motivation, relative advantage, and belief in the future potential of the application, are the main factors supporting usage behavior. Effort expectations include perceived ease and complexity of information can be a factor that supports behavioral intentions. Social support from family and friends and application conditions can also influence ELSIMIL usage behavior